Anaphylaxis and hypersensitivity reactions - Castells, Mariana C. (Humana Press, 2011)
Despite wide recognition as a serious public health problem, anaphylaxis and hypersensitivity reactions remain under-recognized and under-diagnosed. This book fills the gaps in our understanding of the identification of triggers, recognition of clinical presentations, understanding of the natural history of these reactions, and selection of treatment strategies including those focused on cellular and molecular targets. The book provides a detailed examination of disease etiology, pathogenesis, and pathophysiology and their correlation to clinical practice. Forefront knowledge of the mediators and mechanisms of anaphylaxis is covered with an emphasis on how new discoveries shape our current and emerging therapies.